Transforming growth factor β: A potential biomarker and therapeutic target of ventricular remodeling - Ma, Yuan (Oncotarget, 2017)
Transforming growth factor β (TGF-β) is a multifunctional cytokine that is synthesized by many types of cells and regulates the cell cycle. Increasing evidence has led to TGF-β receiving increased and deserved attention in recent years because it may play a potentially novel and critical role in the development and progression of myocardial fibrosis and the subsequent progress of ventricular remodeling (VR). Numerous studies have highlighted a crucial role of TGF-β in VR and suggest potential therapeutic targets of the TGF-β signaling pathways for VR. Changes in TGF-β activity may elicit anti-VR activity and may serve as a novel therapeutic target for VR therapy. This review we discusses the smad-dependent signaling pathway, such as TGF-β/Smads, TGF-β/Sirtuins, TGF-β/BMP, TGF-β/miRNAs, TGF-β/MAPK, and Smad-independent signaling pathway of TGF-β, such as TGF-β/PI3K/Akt, TGF-β/Rho/ROCK,TGF-β/Wnt/β-catenin in the cardiac fibrosis and subsequent progression of VR. Furthermore, agonists and antagonists of TGF-β as potential therapeutic targets in VR are also described.